Sri Lanka : Report on the Observance of Standards and Codes for Anti-Money Laundering and Combating the Financing of Terrorism and Mutual Evaluation Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2008)
The experts reviewed the institutional framework, the relevant Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) laws, regulations, guidelines, and other requirements, and the regulatory and other systems in place to deter money laundering (ML) and the financing of terrorism (FT) through financial institutions and designated non-financial businesses and professions (DNFBP), as well as examining the capacity, the implementation, and the effectiveness of all these systems. The report also analyzes that to curtail the activities of the Liberation Tigers of Tamil Eelam (LTTE), it is necessary to put in place effective measures in respect of AML/CFT.